2005
DOI: 10.1137/040613950
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of the Mimetic Finite Difference Method for Diffusion Problems on Polyhedral Meshes

Abstract: The stability and convergence properties of the mimetic finite difference method for diffusion-type problems on polyhedral meshes are analyzed. The optimal convergence rates for the scalar and vector variables in the mixed formulation of the problem are proved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
384
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(385 citation statements)
references
References 20 publications
1
384
0
Order By: Relevance
“…Eymard et al [36], Aavatsmark et al [1], or Droniou and Eymard [32], mimetic finite difference; cf. Brezzi et al [21], covolume; cf. Chou et al [27], and others.…”
Section: Introductionmentioning
confidence: 98%
“…Eymard et al [36], Aavatsmark et al [1], or Droniou and Eymard [32], mimetic finite difference; cf. Brezzi et al [21], covolume; cf. Chou et al [27], and others.…”
Section: Introductionmentioning
confidence: 98%
“…However, the monotonicity of the lumped MHFE method on general quadrangular meshing can be improved by considering each quadrilateral as a macroelement of triangles. The idea of fictitious subdivision into triangles has already been discussed for mixed finite elements [Brezzi and Fortin, 1991;Kuznetsov and Repin, 2003;Kuznetsov and Repin, 2005;Jaffré et al, 2006] and used in the mimetic finite element/finite difference methods [Kuznetsov et al, 2004;Lipnikov et al, 2006;Brezzi et al, 2005aBrezzi et al, , 2005b.…”
Section: A Technique For Improving the Stability Of Quadrangular Mhfementioning
confidence: 99%
“…(4) Anisotropic discontinuous conductivity tensors are treated in a consistent way, like with finite elements. Note that recently, other conservative numerical methods for flow in porous media have been developed [Edwards, 2002], such as the control volume mixed finite element method [Cai et al, 1997;Klausen and Russell, 2005], the support operator method [Hyman et al, 1997;Berndt et al, 2001], the multipoint flux approximation method [Aavatsmark et al, 1994;Edwards andRogers, 1994, 1998;Aavatsmark, 2002], and the mimetic finite difference method [Kuznetsov et al, 2004;Brezzi et al, 2005aBrezzi et al, , 2005bLipnikov et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Further connections between direct and conforming methods can be established by choosing specific quadrature points to compute the integrals in the conforming method [12,13,19]. Note that quadrature selection can be interpreted as yet another choice for the reconstruction operator.…”
Section: Conforming Mimetic Discretizationmentioning
confidence: 99%
“…Further research also revealed connections between some compatible methods. For instance, mimetic FD for the Poisson equation can be obtained from mixed FE by quadrature choice [12,13,19]. Another example is the equivalence between a covolume method and the classical Marker-and-Cell (MAC) scheme on uniform grids [43] and the analysis of [39] that relates finite volume and finite elements by using the concept of a "spread cell".…”
mentioning
confidence: 99%